Over Three Hundred Gallstones Removed Through Difficult Cholecystectomy - A Case Report - Kostovski, Ognen; Kostovska, Irena (Romanian Society of Surgery - Celsius publisher, 2025)
Background: Cholelithiasis is a common gastrointestinal condition that significantly burdens healthcare systems worldwide. The primary cause of gallstone production is cholesterol hypersaturation. Age and female sex are considered more potent risk factors than other factors, but recent studies presented strong associations between cholesterol gallstones and obesity. Case report: We present a case of a 49-year-old male patient with acute onset intensive abdominal pain in the right upper quadrant. Physical examination, abdominal ultrasound, and laboratory analyses confirmed the diagnosis of acute cholecystitis. The cholecystectomy was done and was found a thickened gall bladder wall with gangrenous mucosa and over 300 gallstones sizes ranging from 2 mm to 5 mm inside it. Conclusions: Clinical examination of the patient, laboratory analyses, and abdominal ultrasound diagnoses are gold-standard diagnostic tools. The mainstay of treatment of symptomatic and asymptotic gallstone diseases is surgery, cholecystectomy.
Keywords: multiple gallstones; acute cholecystitis; cholecystectomy